Association between Hypertensive Disorders of Pregnancy and Long-Term Neurodevelopmental Outcomes in the Offspring - Palatnik, Anna; Mele, Lisa; Casey, Brian M.; Varner, Michael W.; Sorokin, Yoram; Reddy, Uma M.; Wapner, Ronald J.; Thorp, John M., Jr.; Saade, George R.; Tita, Alan T. N.; Rouse, Dwight J.; Sibai, Baha; Costantine, Maged M.; Mercer, Brian M.; Tolosa, Jorge E.; Caritis, Steve N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units Network, Bethesda, MD, USA (American Journal of Perinatology, 2021)
Objective The long-term impact of hypertensive disorders of pregnancy (HDP) exposure on offspring health is an emerging research area. The objective of this study was to evaluate the association between a maternal diagnosis of HDP (gestational hypertension and preeclampsia) and adverse neurodevelopmental outcomes in the offspring.Study Design This was a secondary analysis of two parallel multicenter clinical trials of thyroxine therapy for subclinical hypothyroid disorders in pregnancy. Women with singleton nonanomalous gestations diagnosed with subclinical hypothyroidism or hypothyroxinemia were randomized to thyroxine therapy or placebo. The primary outcome was child intelligence quotient (IQ) at 5 years of age. Secondary outcomes included several neurodevelopmental measures, including the Bayley-III cognitive, motor, and language scores at 12 and 24 months, Differential Ability Scales-II (DAS-II) scores at 36 months, the Conners' rating scales-revised at 48 months, and scores from the Child Behavior Checklist at 36 and 60 months. Thyroxine therapy did not influence neurodevelopment in either of the primary studies. Associations between neurodevelopment outcomes and maternal HDP were examined using univariable and multivariable analyses.Results A total of 112 woman–child dyads with HDP were compared with 1,067 woman–child dyads without HDP. In univariable analysis, mean maternal age (26.7 ± 5.9 vs. 27.8 ± 5.7 years, p = 0.032) and the frequency of nulliparity (45.5 vs. 31.0%, p = 0.002) differed significantly between the two groups. Maternal socioeconomic characteristics did not differ between the groups. After adjusting for potential confounders, there were no significant differences in any primary or secondary neurodevelopment outcome between offspring exposed to HDP and those unexposed. However, when dichotomized as low or high scores, we found higher rates of language delay (language scores <85: −1 standard deviation) at 2 years of age among offspring exposed to HDP compared with those unexposed (46.5 vs. 30.5%, adjusted odds ratio = 2.22, 95% confidence interval [CI]: 1.44–3.42).Conclusion In this cohort of pregnant women, HDP diagnosis was associated with language delay at 2 years of age. However, other long-term neurodevelopmental outcomes in offspring were not associated with HDP.Key Points
Keywords: hypertensive disorders of pregnancy; neurodevelopmental outcomes; intelligence quotient; language delay; in utero exposure